1980
DOI: 10.1227/00006123-198012000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Value of Computed Tomography in the Prediction of Cerebral Vasospasm after Aneurysm Rupture

Abstract: The relationship between high density (HD) on computed tomographic (CT) scans (which indicates a collection of blood in the subarachnoid space) and cerebral vasospasm was studied in 177 patients with ruptured aneurysm. The development of cerebral vasospasm was confirmed at the high rate of 84.6% in 26 cases where HD was demonstrated on the CT scan within 4 days after subarachnoid hemorrhage (SAH). In 8 cases where HD was not found on the CT scan obtained within 4 days after SAH, no cerebral vasospasm was seen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…They named this phenomenon the "biphasic response." 10 Since then, many reports have noted the same phenomenon in various animal models. In our…”
Section: Discussionmentioning
confidence: 83%
“…They named this phenomenon the "biphasic response." 10 Since then, many reports have noted the same phenomenon in various animal models. In our…”
Section: Discussionmentioning
confidence: 83%
“…Clotted blood may be localized to one or more cisterns or spread throughout the subarachnoid space, depending upon the configuration of the cisterns which can vary from patient to patient 33. Both clinical and experimental studies have demonstrated that the degree and duration of spasm correlate with the amount of locally accumulated blood in the subarachnoid space 9, l a, 15,19,26. The present model in the squirrel monkey represents an effort to achieve an accumulation of blood around the circle of Willis simulating SAH in patients.…”
Section: Discussionmentioning
confidence: 94%
“…AFs have been considered: a) to increase the rate of intravascular sludging, favouring the formation platelet-fibrin emboli and microthrombi associated with arterial narrowing, and/or b) to worsen or increase the incidence of vasospasm by reducing the clearance of blood from the subarachnoid space, thus allowing the blood to remain in the cisterns and to exert vasoconstrictor effects. It is now well known that a consistent amount of blood-especially clotted blood-in the cisterns, as documented by CT scan, is a finding associated with a significantly higher risk of developing ischaemic deficits from vasospasm 11' 2s, 29,35,47. It has also been suggested that persistence of cisternal blood on CT scan at more than 72 hours from SAH may further increase the risk of vasospasm 35.…”
Section: ) Evaluation Of Complicationsmentioning
confidence: 99%